(untitled) - Nurtas B. SMAGULOV, Aray K. ZHUNDIBAYEVA, Satay M. SIZDIKOV, Arap S. YESPENBETOV, Ardak K. KAPYSHEV (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Purpose of the study. Studying and evaluating the activities of Tonykuk, who was the state adviser to the Second Turkic Kaganate, the main ideologist responsible for the ideological activities of the Kaganate from 682 to 745, is an urgent problem of historical science. In the years 646-725 he worked as an adviser on political and cultural issues of the three Kagan. The work reveals the essence of the secrets of the activities of Tonykuk, who was a state adviser and chairman of the Supreme Court. The purpose of the study is to analyze the activities of Tonykuk and identify the origin of the national idea of all ethnic groups living in Kazakhstan. Methodology. In the course of work, historical archives were studied, as well as the strodes of historians involved in the issues of the Turkic Kaganate. The paper analyzes the ethnic origin, ethnogenesis, tribal composition, state structure of the ancient Turks. Main findings. The article reveals the essence of the secrets of the activities of Tonykuk, who was a state adviser and chairman of the Supreme Court. Social Implications. The study shows how the nationwide idea of all the ethnic groups inhabiting Kazakhstan was born. Originality/Novelty of the study. Currently, there is relatively little research into the activities of Tonykuk as a historical figure. Comprehensive studies of the origin of the national idea of all ethnic groups inhabiting Kazakhstan in the context of historical events and activities of Tonykuk were not found in the analysis of previous studies.